Public relation activities in Islamic banking industry: An approach of Circuit of Culture (COC) Model - Mohd Thas Thaker, M. A.; Mohd Thas Thaker, Hassanudin *; Anwar, A. P. (Emerald, 2018)
Purpose:This paper has adopted Circuit of Culture (COC) model as theoretical framework to examine the role of religion in influencing the public relations activity of Islamic banking institutions in Malaysia. Design/methodology/approach: A narrative analysis is used in this study. This analysis is basically involved the application of symbolic interactionist tenets to respective websites and relevant documents of Islamic banks in Malaysia. Findings: The paper has identified six Islamic value orientations elements, especially respect for religious authority, affinity with the past, fatalism, communal kinship, attachment to the eternal life and spirituality and idealism relative to public relations practice among the Islamic banks in Malaysia. The study finds that the respective banks are embedded with Islamic values in their communication tools that reflecting public relations activity. Research limitations/implications – The theme of value orientations that have been generated and used in this study are constantly in flux. There are some other orientations that might be affecting the cultural value of public relations activities of Islamic banking in Malaysia. Furthermore, these value orientations are less effective in identifying dominating cultural factors that can be amended with situational flexibility since the current study focuses on Malaysian context. Future research is required by incorporating a quantitative means of testing and measuring the effectiveness of website by using cultural- economic model for building Practical implications: The study suggests that public relations researchers should not ignore the vital relationship between religion and public relations activity. The findings of this paper provide Islamic banking institutions to improve and enhance their public relations activity. Originality/value – This paper offers an additional literature related to public relations activity by employing Cultural-Economic model. While previous studies have focused on product, brand matters and organisation behavior to define cultural and public relation, very little research has been focused on the role of religion in determining public relations activity and cultural pattern. Indeed, no any study have been focused explicitly on public relations activity of Islamic banks in Malaysia using Circuit of Culture (COC).